THE USE OF CODE MIXING IN INDONESIAN NOVEL ENTITLED YOU DO YOU BY FELLEXANDRO RUBY - Al-furqon, Achmad Syarofi (Universitas Madura, 2024)
Since Indonesia has been a multilingual country, many people in this country use more than one language in the daily conversation. Bilingualism and multilingualism are common in Indonesia. Code mixing happens when the speaker mixes their first language with the second language in one utterance, It is just a normal requirement of daily living that people speak several languages: perhaps one or more at home, another in the village, still another for purposes of trade, and yet another for contact with the outside world of wider social or political organization. Code mixing is also found in Indonesian novel entitled You Do You by Fellexandro Ruby. The researcher is interested to find what kinds of code mixing that the characters’ used in this novel. The result of this study found that there are three kinds of type code mixing, that the character mostly used, they are Insertion, Alteration and Congruent Lexicalization.